Dealloyed nanoporous platinum films: synthesis, characterization, and hydrogen sensing properties - Sener, Melike; Altuntepe, Ali; Zan, Recep; Kilinc, Necmettin (Frontiers in Nanotechnology, 2025)
Nanoporous platinum (Pt) films are synthesized at room temperature using a straightforward and cost-effective dealloying technique. This method is suitable for producing various nanoporous materials for diverse applications. Copper (Cu) atoms in the PtCu alloy films were selectively dissolved in a nitric acid solution, at varying times, to obtain nanoporous films. PtCu alloy thin films were then deposited onto a glass substrate utilizing the magnetron co-sputtering method with approximately 50 nm thickness. After 20 h dealloying in the acid solution, the residual Cu content in the alloy was less than 1% (atomic rate), and a regular nanoporous Pt structure was observed. The hydrogen detection properties of the nanoporous Pt films thus produced were investigated at various temperatures within a concentration range between 10 ppm and 5% hydrogen. The results demonstrated that a very high sensor response of 64 was obtained for the first exposure to 1% hydrogen at 150 °C, but the nanoporous Pt sensor resistance did not return to the baseline resistance. To utilize this nanoporous Pt film as a reversible hydrogen sensor, the film must be pre-exposed to hydrogen. After pre-exposure, the sensor response of the as-prepared nanoporous Pt was approximately 4.5, resulting from exposure to 1% hydrogen at 150 °C, and the limit of detection was lower than 10 ppm. Data regarding the mechanism of the nanoporous Pt sensor device were clarified through surface scattering. The main contributions of this research are that sensing nanoporous film has a high surface-to-volume ratio, the sensor exhibited a very high initial response (∼64) to 1% hydrogen at 150 °C, the sensor mechanism is governed by surface scattering, and pre-exposure to hydrogen is needed for reversible sensing operation in practical usage.